2002
DOI: 10.1128/jvi.76.7.3318-3328.2002
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Characterization of a Dengue Type 1 Host Range-Restricted Mutant Virus That Is Attenuated and Highly Immunogenic in Monkeys

Abstract: We recently described the derivation of a dengue serotype 2 virus (DEN2mutF) that exhibited a host range-restricted phenotype; it was severely impaired for replication in cultured mosquito cells (C6/36 cells). DEN2mutF virus had selected mutations in genomic sequences predicted to form a 3 stem-loop structure (3-SL) that is conserved among all flavivirus species. The 3-SL constitutes the downstream terminal ϳ95 nucleotides of the 3 noncoding region in flavivirus RNA. Here we report the introduction of these sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 41 publications
(53 reference statements)
2
18
1
Order By: Relevance
“…Although monkeys inoculated with rDEN1mutF showed a decreased level of viremia compared to those inoculated with wt rDEN1, this difference was not statistically significant. Previously published results for studies with rhesus monkeys have shown a similar level of attenuation for rDEN1mutF (11). In addition, Markoff et al have shown that there was a difference in the mean number of days of viremia (determined by reverse transcription-PCR) between monkeys that received DEN1mutF virus and those that received wt DEN1 (11).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Although monkeys inoculated with rDEN1mutF showed a decreased level of viremia compared to those inoculated with wt rDEN1, this difference was not statistically significant. Previously published results for studies with rhesus monkeys have shown a similar level of attenuation for rDEN1mutF (11). In addition, Markoff et al have shown that there was a difference in the mean number of days of viremia (determined by reverse transcription-PCR) between monkeys that received DEN1mutF virus and those that received wt DEN1 (11).…”
mentioning
confidence: 63%
“…1A). The use of wt DEN1 virus as the parent for the introduction of the ⌬30 mutation also permitted a comparison of the level of attenuation of rDEN1⌬30 with that of the previously described rDEN1mutF virus, which also contains mutations in the 3Ј UTR (11). The mutF mutation consists of a pair of deleted nucleotides and a two-nucleotide substitution in the terminal 3Ј stem-loop structure conserved among all flavivirus species (22).…”
mentioning
confidence: 99%
“…Specifically, modification of the 3'-UTR as a means to attenuate DENV has resulted in the development of several promising live attenuated vaccine candidates [19,22,32,33]. The introduction of deletion mutations into untranslated regions is an attractive strategy for development of live attenuated DENV vaccines for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies indicate that variations in the 3Ј NCR are well tolerated but may sometimes lead to altered growth characteristics in cell culture (3,6,19), changes in virulence and immunogenicity in vertebrate animals (10,17,21,22), or reduced infectivity in mosquitoes (1,44). Molecular epidemiological studies of naturally occurring flaviviruses also suggest that 3Ј NCR structural differences correlate with patterns of virus distribution and transmission (39,50).…”
mentioning
confidence: 99%